Changing incentives in a multitask environment: evidence from a top-tier business school - Brickley, James A; Zimmerman, Jerold L (Journal of Corporate Finance, 2001)
This study focuses on changes in incentives at the William E. Simon Graduate School of Business Administration in the early 1990s to redirect effort from academic research to classroom teaching. We find a substantial and almost immediate jump in teaching ratings following the changes in incentives. Longer-run learning and turnover effects are present. Evidence also suggests that research output fell. This case illustrates the power of organizational incentives to redirect effort in a multitask environment, even in the presence of apparent human–capital constraints.